2011
DOI: 10.1038/npp.2011.250
|View full text |Cite
|
Sign up to set email alerts
|

Gray Matter Volumes in Obsessive-Compulsive Disorder Before and After Fluoxetine or Cognitive-Behavior Therapy: A Randomized Clinical Trial

Abstract: Serotonin reuptake inhibitors and cognitive-behavior therapy (CBT) are considered first-line treatments for obsessive-compulsive disorder (OCD). However, little is known about their modulatory effects on regional brain morphology in OCD patients. We sought to document structural brain abnormalities in treatment-naive OCD patients and to determine the effects of pharmacological and cognitive-behavioral treatments on regional brain volumes. Treatment-naive patients with OCD (n=38) underwent structural magnetic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
71
3
10

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(91 citation statements)
references
References 77 publications
4
71
3
10
Order By: Relevance
“…Evidence from electrophysiology and neuroimaging (1) studies has long indicated the involvement of the basal ganglia in OCD. Greater putamen and caudate volume is often (2-5) but not consistently found, and findings may be dependent on the age of the recruited samples, treatment history, or treatment status (12). We did not find striatal volume alterations in the overall OCD patient group, but in line with a previous report (8), we observed a relatively preserved volume of the putamen and nucleus accumbens during aging in patients.…”
Section: Altered Brain Volume Changes In Ocd During Agingsupporting
confidence: 87%
See 1 more Smart Citation
“…Evidence from electrophysiology and neuroimaging (1) studies has long indicated the involvement of the basal ganglia in OCD. Greater putamen and caudate volume is often (2-5) but not consistently found, and findings may be dependent on the age of the recruited samples, treatment history, or treatment status (12). We did not find striatal volume alterations in the overall OCD patient group, but in line with a previous report (8), we observed a relatively preserved volume of the putamen and nucleus accumbens during aging in patients.…”
Section: Altered Brain Volume Changes In Ocd During Agingsupporting
confidence: 87%
“…Moreover, only the middle frontal gray matter finding (a region not overlapping with the main group effects) remained significant after we controlled for the differing sample characteristics of the medicated versus unmedicated patients in a multiple regression analysis. Therefore, it is possible that gray matter alterations in the middle frontal cortex may be partially attributable to current medication use, a finding that deserves further investigation, ideally using longitudinal designs (12).…”
Section: Association With Clinical Characteristicsmentioning
confidence: 99%
“…7,56,57 However, although our sample was partly medicated and not comorbidity-free, these factors did not show any significant effect on the present results after correcting for multiple comparisons. Considering that on an uncorrected threshold an effect was found in certain clusters, it cannot be excluded that comorbidity or medical treatment had a certain influence on grey matter structure.…”
Section: Limitationscontrasting
confidence: 58%
“…Antes do tratamento, os pacientes com TOC apresentavam menor substância cinzenta no putâmen esquerdo, no cór-tex orbitofrontal medial bilateral e no córtex cingulado anterior esquerdo em comparação com os controles. Após o tratamento, tanto pacientes tratados com fluoxetina quanto TCC não apresentavam diferença em relação aos controles na quantidade de substância cinzenta no putâmen esquerdo (Hoexter et al, 2012).…”
Section: Evidências De Modifi Cações Neuroanatômicas E Funcionais No unclassified